Mold design for plastics injection molding process (two colors) and analysis of gates location - Ahmad Zulhelmi, Muhamad (2009)
This thesis describe about the mold design for plastic injection molding process for two colors and the analysis of gate location in order to find the best gate location to apply it in to the design. The molds for injection molding is not the cheap one it is expensive and needed an accurate step when apply the design on the mold because a slice mistake can follow by big loss. First step is about finding the best gate location from several gate location have been choose but before that the design of the product and it materials should be choose. After the analysis have done, the collected data from several gate location will be compare in order to find best gate location and apply it in the mold design. To designing mold, the several system like runner system, injector system and the ways material enter the mold will be considered.